2020
DOI: 10.1111/ntwe.12181
|View full text |Cite
|
Sign up to set email alerts
|

Political campaigns on YouTube: trade unions’ mobilisation in Europe

Abstract: Trade unions are called to increase their influence on policy‐making by becoming more politically active and use social media, but only a few studies investigate unions’ online political activism. We propose that industrial relations regime of a country relates to unions’ perceived opportunities for mobilisation and thereby also unions’ online political activism. We test this argument with the help of data about European trade union confederations’ political mobilisation on YouTube, 2007–2017. The results show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 59 publications
(62 reference statements)
1
1
0
1
Order By: Relevance
“…Theoretically, this again supports Metz's statement that the level of selfpersonalisation seen in politicians, social media is highly dependent on the context of the country in which the politician is located (Metz et al, 2019). Likewise, in Uba's study about how the public uses social media as a channel for a political campaign, specifically how trade unions use YouTube for influencing policymaking, it was found that the intensity of online political mobilisation and online election campaigning differ across regimes in Europe (Uba & Jansson, 2021). Taken together, these findings might suggest the importance of the context of the country or area in which the online political campaign is conducted.…”
Section: Discussionsupporting
confidence: 71%
“…Theoretically, this again supports Metz's statement that the level of selfpersonalisation seen in politicians, social media is highly dependent on the context of the country in which the politician is located (Metz et al, 2019). Likewise, in Uba's study about how the public uses social media as a channel for a political campaign, specifically how trade unions use YouTube for influencing policymaking, it was found that the intensity of online political mobilisation and online election campaigning differ across regimes in Europe (Uba & Jansson, 2021). Taken together, these findings might suggest the importance of the context of the country or area in which the online political campaign is conducted.…”
Section: Discussionsupporting
confidence: 71%
“…Sosiaalisen median poliittista potentiaalia tukea puolueiden jäsenten ja kansalaisten mahdollisuuksia osallisuuteen ja vaikuttamiseen voidaan pitää yhä merkittävämpänä (de Nadal 2021; Uba & Jansson 2021;Zhuravskaya ym. 2020).…”
Section: Puolueiden Sivistykselliset Roolitunclassified
“…The sixth article by Uba and Jansson (2021) focuses on the online political action of confederations as a way to increase the political influence of the trade union movement. More specifically, the study seeks to understand the ways in which the industrial relations context shapes the political action of confederations on YouTube in twenty‐six European countries between 2007 and 2017.…”
Section: Contributions To the Special Issuementioning
confidence: 99%